Assessment of Particle Size on the Physico-mechanical Behavior of Waste Low-Density Polyethylene/Delonix regia Seed Composite - Bakare, Ayuba; Lawal, Nuhu; Andrew, Paul Mamza; Akuaden, Ephraim Audu; Asimi, Sulaiman; Abiodun, Emmanuel Oyekanmi; Yakubu, Abdulmajeed Muhammad (Journal of Fibers and Polymer Composites, 2025)
The excessive and widespread usage of single-use plastics has led to a growing concern over the accumulation of non-biodegradable waste in natural environments, posing a serious threat to global ecosystems. Incorporating agricultural residues into polymer composites as reinforcements presents a sustainable alternative, offering benefits such as low cost, ease of processing, reduced environmental impact, lightweight characteristics, and biodegradability. This research investigates how the particle size of Delonix regia (D.regia) seed waste influences the physico-mechanical properties of a composite made from waste low density polyethylene (wLDPE). The study found that increasing the particle size of the filler led to a gradual reduction in tensile strength, elongation at break, flexural strength, and density of the composite by 15.75 %, 75.93 %, 24.08 % and 14.08 % respectively. Conversely, larger filler particles enhanced the composite’s hardness and impact resistance by 56.16 % and 76.07 % respectively. Additionally, water absorption increased with particle size, with the highest uptake observed in composites containing the largest particles and lowest in composites containing smallest particles.